HAK RESTITUSI BAGI KORBAN KEJAHATAN KORPORASI - Rohmah, Adinda Syifa’u; Zulkarnain, Aini Jatsiyah; Susanti, Pipi (Cahaya Ilmu Bangsa, 2024)
Restitution is a loss recovery mechanism for victims of corporate crime, which is regulated in various laws and regulations, especially PERMA Number 13 of 2016 concerning Procedures for Handling Criminal Cases by Corporations. This mechanism allows victims to obtain compensation in the form of return of property, compensation, or reimbursement of costs provided by the perpetrator or third party through a judge's decision, with the aim of returning the victim to the original condition before the crime occurred. The implementation of Law No. 31/2014 on Witness and Victim Protection still faces challenges, especially in dealing with complex corporate crimes. Law enforcement agencies need to increase capacity, both in terms of human resources and infrastructure, to ensure victims get justice and proper recovery. Fulfilling the right to restitution requires a comprehensive, sustainable approach and full support from all parties. Restitusi merupakan mekanisme pemulihan kerugian bagi korban tindak pidana korporasi, yang diatur dalam berbagai peraturan perundang-undangan, khususnya PERMA Nomor 13 Tahun 2016. Mekanisme ini memungkinkan korban memperoleh kompensasi berupa pengembalian harta, ganti kerugian, atau penggantian biaya yang diberikan oleh pelaku atau pihak ketiga melalui putusan hakim, dengan tujuan mengembalikan korban pada kondisi semula sebelum terjadinya kejahatan. Lalu, implementasi dari Undang-Undang Nomor 31 Tahun 2014 tentang Perlindungan Saksi dan Korban masih menghadapi tantangan, terutama dalam menangani kejahatan korporasi yang kompleks. Lembaga penegak hukum perlu meningkatkan kapasitas, baik dalam hal sumber daya manusia maupun infrastruktur, untuk memastikan korban mendapatkan keadilan dan pemulihan yang layak. Pemenuhan hak restitusi membutuhkan pendekatan menyeluruh, berkelanjutan, dan dukungan penuh dari semua pihak.